Tensões e contribuições do estágio curricular na constituição da identidade profissional do licenciando em Matemática na EaD : Tensions and contributions of the curricular internship in the constitution of the professional identify of the future mathematics teacher in distance learning courses - Costa, Priscila Kabbaz Alves da, 1982- (2018)
Orientadores: Dario Fiorentini, Carlos Miguel da Silva Ribeiro